Effects of coach-delivered verbal encouragement on the physiological and psychological responses of adolescent players in small-sided basketball games - Khayati, Ala; Sahli, Faten; Ghouili, Hatem; Labbadi, Rabeh; Selmi, Okba; Sahli, Hajer; Jebabli, Nidhal; Romdhani, Amir; Zghibi, Makram; Haddad, Monoem (Frontiers in Psychology, 2024)
Introduction The confluence of physiological and psychological dynamics is fundamental to athletic performance, particularly in basketball, where physical skill and mental resilience are imperative. While the role of verbal encouragement (VE) as a catalyst for enhancing performance has been explored in various sports disciplines, its specific effects within the basketball have not been adequately examined. Addressing this gap, the current study zeroes in on the influence of coach-delivered VE on the physiological and psychological responses of adolescent basketball players engaged in small-sided games (SSG), providing a focused analysis of how directed encouragement can modulate performance and experience in young athletes. This study aimed to investigate the effects of coach-delivered verbal encouragement on the psychological and physiological responses of adolescent basketball players. Methods Sixteen male participants (age: 16.93 ± 0.36 years; height: 176.8 ± 0.8 cm; body mass: 73.43 ± 12.57 kg; BMI: 21.70 ± 3.55) were allocated to a Verbal Encouragement Group (VEG, n = 8, mean age: 16.80 ± 0.44) and a Control Group (CG, n = 8, mean age: 17.06 ± 0.26). Each participant engaged in four sessions of small-sided games (SSGs) consisting of four players per side in a 14 × 10 m pitch. Results The findings revealed significant benefits of coach-delivered verbal encouragement on both the physical and psychophysiological responses of the players (p < 0.05), including increased physical enjoyment, positive mood state, lower heart rate, and higher physical activity intensity level. Discussion Coaches should incorporate verbal encouragement strategies during SSGs to enhance player performance and optimize both psychological and physiological adaptations.